(untitled) (Dhaka Shishu (Children) Hospital Journal, 2020)
Dengue viruses cause symptomatic infections or asymptomatic seroconversion. Symptomatic dengue infection is a systemic and dynamic disease. It has a wide clinical spectrum that includes both severe and non-severe clinical manifestations. Due to its dynamic nature, the severity of the disease will usually only be apparent around defervescence which often coincides with the onset of the critical phase. For a disease that is complex in its manifestations, management is relatively simple, inexpensive and very effective in saving lives, so long as correct and timely interventions are instituted. The main hemodynamic elements of dengue shock is hypovolemia with decreased vascular capacitance resulting from plasma leakage. Thus, the strategy of aggressive fluid resuscitation of septic shock is not applicable to severe dengue with plasma leakage. Volume replacement in children with dengue shock is a challenging management problem. Aggressive fluid resuscitation may indeed be harmful and should be limited to dengue shock with hypotension. There is a “narrow therapeutic index”; therefore, fluids have to be given timely, at the appropriate volume, rate, of the appropriate type (crystalloids, colloid and/or blood) and for the appropriate duration. Therein lies the challenge to physicians who are not familiar with the important practice of fluid titration through frequent and meticulous assessment. Progression of the disease through the critical phase should be tracked in hours of plasma leakage. Recognizing the cues to discontinue intravenous fluid therapy is just as important as knowing when to start it. Given time and hemodynamic stability, other issues such as thrombocytopenia, coagulopathy and raised liver enzymes will recover spontaneously or with supportive care. DS (Child) H J 2019; 35(2) : 162-178